PROPAGATION OF Cotoneaster prostrata BY STEM CUTTINGS - G. Y. Al-Noaimy (Mesopotamia Journal of Agriculture)
This investigation was conducted in green house of Department of Horticulture , College of Agriculture and Forestry , Mosul University . The aim of this work is to study the effects of four planting date, August , November , February and May after treated the cutting with IBA+NAA mixture at 0+0 ( control ) , 1000+1000 and 1500+1500 mg /l in quick – dip method ,in addition to wounding or without . The results of this investigation were showed that planting date had a great effect on rooting , planting the cuttings in February and November gave 88.19 and 100 % . All rooting characters were improved when the cuttings wounded before planting . On other hand , the cuttings treated with a mixture of IBA+NAA at concentration 1000+1000 mg/l gave best results 70.31% largest number of roots per cutting 7.19 longest roots 5.19 cm and largest number of shoot 0.54 shoot/ cutting . by wounding the terminal cuttings of Cotoneaster prostrata and planted in November and February treated with a mixture of IBA+NAA at concentration 1000+1000 mg / l gave best result for rooting and vegetative growth.